2018
DOI: 10.1039/c8md00147b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of new 3-amino-2-azetidinone derivatives as anti-colorectal cancer agents

Abstract: Several synthetic combretastatin A4 () derivatives were recently prepared to increase the drug efficacy and stability of the natural product isolated from the South African tree . A group of ten 3-amino-2-azetidinone derivatives, as combretastatin A4 analogues, was selected through docking experiments, synthesized and tested for their anti-proliferative activity against the colon cancer SW48 cell line. These molecules, through the formation of amide bonds in position 3, allow the synthesis of various derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In addition, the trimethoxyphenyl group is a well-known fragment in some natural tubulin polymerization inhibitors, such as CA-4, colchicine, and podophyllotoxin (Figure ). The 3,4,5-trimethoxyphenyl group can be linked to another aromatic system and is the only well-defined pharmacophore for the inhibition of tubulin polymerization …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the trimethoxyphenyl group is a well-known fragment in some natural tubulin polymerization inhibitors, such as CA-4, colchicine, and podophyllotoxin (Figure ). The 3,4,5-trimethoxyphenyl group can be linked to another aromatic system and is the only well-defined pharmacophore for the inhibition of tubulin polymerization …”
Section: Introductionmentioning
confidence: 99%
“…25 Studies on molecular targets and docking calculations suggested that these imidazolium salt hybrids may be mammalian target of rapamycin (mTOR) signaling inhibitors. 25−27 In addition, the trimethoxyphenyl group is a well-known fragment in some natural tubulin polymerization inhibitors, 30−32 such as CA-4, 30 colchicine, 31 and podophyllotoxin 32 (Figure 1). The 3,4,5-trimethoxyphenyl group can be linked to another aromatic system and is the only well-defined pharmacophore for the inhibition of tubulin polymerization.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Two of the selected compounds are β-lactams: PGC22i is a penicillin and CIT171B3 is a monobactam. Both, penicillin compounds [9,17,21] and monobactams [22][23][24], have demonstrated antitumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, drug resistance remains a challenge, leading to the failure of CRC treatment ( 4 ). In addition to gaining an understanding of the mechanism of intrinsic and acquired therapy resistance, researchers have focused on small-molecule compounds that induce less toxicity and have greater efficacy for cancer treatment ( 5 , 6 ). In our previous study, a chemical library obtained from ChemBridge Corporation was screened for potential novel anticancer agents.…”
Section: Introductionmentioning
confidence: 99%